Resilienssin käsite ja operationalisointi – case liikennejärjestelmä [Resilience and its operationalization – case transport system] - Leviakangas, Pekka; Aapaoja, A. (2015)
This paper introduces a generic resilience framework that is applied to transport systems. The framework is based on prior research and literature on resilience. The paper first reviews the relevant literature and builds a resilience model that distinguishes the attributes and sub-attributes of resilience. The resilience model and transport system components are then merged into a single-system resilience matrix. The complexity of resilience of a meta-system – a system comprising several sub-systems – is discussed in brief and a simplified example of how to apply meta-level resilience analysis on transport systems is shown. Finally, the implications for other systems, particularly those governed by cities and municipalities, are discussed. In fact, cities and municipalities face even more complex resilience analysis tasks than those faced by State authorities, who mostly govern sector systems (e.g. transport) within their mandate. It is argued that municipal decision-makers encounter serious challenges and questions when they consider the enhancement of their communities’ resilience.